Structural Behavior of Concrete One-Way Slab with Mixed Reinforcement of Steel and Glass Fiber Polymer Bars under Fire Exposure - Rasheed, Mohammed R.; Mohammed, Shatha D. (Engineering, Technology & Applied Science Research, 2024)
Steel Reinforced Concrete (RC) frequently faces durability problems. In certain areas, Glass Fiber-Reinforced Polymer (GFRP) rebars are considered a non-corrodible substitute for steel reinforcement. Elevated temperatures have a significant impact on the mechanical characteristics and the adhesiveness of GFRP rebars to concrete, particularly when the polymeric matrix’s glass transition temperature is approached or surpassed. Three simply supported reinforced concrete slabs were considered in the experimental program. Each specimen had identical dimensions of 1500×540×120 mm. For the fire resistance requirements, a 45 mm clear concrete cover and an exception of a 200 mm unexposed (cool) anchor zone at the ends were considered. The GFRP replacement ratio was 0, 20, and 40%. The burning procedure involved fire exposure for an hour with a steady-state temperature of 500 °C in accordance with ASTM E-119 regarding the temperature time elevation and a sudden cooling condition. The optimal concrete cover was detected by testing a fire-exposed small model reinforced by GFRP bars of varying concrete cover. The specimen was tested under static intense loads. The reference slab and the slab with a replacement percentage of 20% failed due to flexural failure, whereas the slab with a replacement percentage of 40% failed due to shear failure. The influence of the GFRP replacement ratio was extended to include toughness and ultimate load. A replacement percent of 20% increased them by 18.30, and 2.62%, respectively, while a replacement percent of 40% decreased them by 28.16, and 3.13%, accordingly. It was also shown that the location of replacing the GFRP and 200 mm of unexposed (cold) installation area at the ends with a 45 mm concrete cover has a significant impact. The more the GFRP is located in the middle, away from the ends, the better the fire resistance is.